Thermal Desorption of Iodine-123 from Tellurium-122 Oxide Irradiated by Deuterons - Skuridin V. S. Viktor Sergeyevich; Garapatski A. A. Alexander Alexandrovich; Slamkulov A.; Semenov A. O. Andrey Olegovich; Ermakova Ya. V. Yanina Viktorovna (2015, 2015)
Title screen